Step
*
1
1
2
1
1
of Lemma
increasing-sequence-converges
1. x : ℕ ⟶ ℝ
2. ∀n:ℕ. ((x n) < (x (n + 1)))
3. c : {2...}
4. m : ℕ+
5. ∀n:ℕ+. (((x (n + 1)) - x n) ≤ ((r1/r(c)) * ((x n) - x (n - 1))))
6. (r(c) * ((x 1) - x 0)/r(c - 1)) ≤ (r1/r(m))
7. n : ℤ
8. 0 < n
9. ((x ((n + 1) + 1)) - x (n + 1)) ≤ ((r1/r(c)) * ((x (n + 1)) - x ((n + 1) - 1)))
10. v : ℝ
11. ((x (n + 1)) - x n) = v ∈ ℝ
12. v1 : ℝ
13. ((x 1) - x 0) = v1 ∈ ℝ
⊢ (v ≤ ((r1/r(c^n)) * v1)) 
⇒ (((r1/r(c)) * v) ≤ ((r1/r(c^n + 1)) * v1))
BY
{ ((D 0 THENA Auto) THEN (nRMul ⌜(r1/r(c))⌝ (-1)⋅ THENA Auto)) }
1
1. x : ℕ ⟶ ℝ
2. ∀n:ℕ. ((x n) < (x (n + 1)))
3. c : {2...}
4. m : ℕ+
5. ∀n:ℕ+. (((x (n + 1)) - x n) ≤ ((r1/r(c)) * ((x n) - x (n - 1))))
6. (r(c) * ((x 1) - x 0)/r(c - 1)) ≤ (r1/r(m))
7. n : ℤ
8. 0 < n
9. ((x ((n + 1) + 1)) - x (n + 1)) ≤ ((r1/r(c)) * ((x (n + 1)) - x ((n + 1) - 1)))
10. v : ℝ
11. ((x (n + 1)) - x n) = v ∈ ℝ
12. v1 : ℝ
13. ((x 1) - x 0) = v1 ∈ ℝ
14. ((r1/r(c)) * v) ≤ ((r1/r(c^n)) * (r1/r(c)) * v1)
⊢ ((r1/r(c)) * v) ≤ ((r1/r(c^n + 1)) * v1)
Latex:
Latex:
1.  x  :  \mBbbN{}  {}\mrightarrow{}  \mBbbR{}
2.  \mforall{}n:\mBbbN{}.  ((x  n)  <  (x  (n  +  1)))
3.  c  :  \{2...\}
4.  m  :  \mBbbN{}\msupplus{}
5.  \mforall{}n:\mBbbN{}\msupplus{}.  (((x  (n  +  1))  -  x  n)  \mleq{}  ((r1/r(c))  *  ((x  n)  -  x  (n  -  1))))
6.  (r(c)  *  ((x  1)  -  x  0)/r(c  -  1))  \mleq{}  (r1/r(m))
7.  n  :  \mBbbZ{}
8.  0  <  n
9.  ((x  ((n  +  1)  +  1))  -  x  (n  +  1))  \mleq{}  ((r1/r(c))  *  ((x  (n  +  1))  -  x  ((n  +  1)  -  1)))
10.  v  :  \mBbbR{}
11.  ((x  (n  +  1))  -  x  n)  =  v
12.  v1  :  \mBbbR{}
13.  ((x  1)  -  x  0)  =  v1
\mvdash{}  (v  \mleq{}  ((r1/r(c\^{}n))  *  v1))  {}\mRightarrow{}  (((r1/r(c))  *  v)  \mleq{}  ((r1/r(c\^{}n  +  1))  *  v1))
By
Latex:
((D  0  THENA  Auto)  THEN  (nRMul  \mkleeneopen{}(r1/r(c))\mkleeneclose{}  (-1)\mcdot{}  THENA  Auto))
Home
Index